Palaeohydrology and its impact on groundwater in arid environments: Gebel Duwi and its vicinities, Eastern Desert, Egypt - Yousif, Mohamed; Henselowsky, Felix; Bubenzer, Olaf (Catena, 2018)
From ancient times, access to water in arid and hyper-arid regions has been crucial for life. Increased knowledge about groundwater conditions is therefore extremely important for the future development of desert areas. Gebel Duwi, a limestone ridge, sited in the today hyper-arid Eastern Desert of Egypt, was chosen for testing current hypotheses concerning the interdependence of palaeohydrologic features and geologic settings for groundwater investigations. Two sub-basins are identified in affecting Gebel Duwi: Wadi Nakheil and Wadi Sodmein. Both have extraordinary high stream order, indicating the reality of a very old drainage system. Several additional palaeohydrologic features such as wadi terraces, alluvial fans, and playa deposits are also recorded in these sub-basins. These features, as well as finds from an important archaeological site (Sodmein Cave), provide information about palaeoenvironmental changes and wetter climatic periods in the younger geologic past, mainly in the Late Pleistocene and Holocene, which have affected the occurrence of present day groundwater. This study combines new results of geological and geomorphological field studies, examinations of digital elevation models, as well as of rock and water analyses in an integrated approach. Resulting maps comprise landforms, lithology, elevation, drainage lines slope, structural lineaments and flow directions. The hydrogeologic condition indicates suitable locations for groundwater recharge and accumulation. The research presented is interdisciplinary in approach and is recommended for future studies with regard to groundwater exploration, sustainable groundwater use, and the protection of archaeological sites in arid lands.